The Role of Gut Microbiota in Hypertension Management - A Review - Kot, Alicja; Wojtczak, Marta; Myśliwiec, Natalia; Różycki, Adrian; Pniak, Michał; Miklis, Paweł; Mawlichanów, Maciej; Ciesielska, Aleksandra; Sieradzka, Aleksandra; Szerej, Krzysztof (Quality in Sport, 2025)
Introduction and purpose: Hypertension, or high blood pressure, is a condition characterized by persistently elevated arterial pressure, leading to severe complications such as heart disease, stroke, and kidney failure. According to the World Health Organization (WHO), hypertension affects approximately 1.13 billion people worldwide, contributing significantly to global morbidity and mortality. Emerging research has revealed a significant connection between gut microbiota—the diverse community of microorganisms residing in the gastrointestinal tract—and the regulation of blood pressure. This comprehensive review explores the intricate relationship between gut microbiota and hypertension, delving into the underlying mechanisms, evidence from animal and human studies, and potential therapeutic interventions. The state of knowledge: Key mechanisms involved into regulation of blood pressure include the production of short- chain fatty acids (SCFAs), modulation of the renin-angiotensin system (RAS), immune system regulation, and metabolite production such as trimethylamine-N-oxide (TMAO). Animal studies using fecal microbiota transplantation (FMT) have provided strong evidence for a causal role of gut microbiota in blood pressure regulation. Human studies have shown associations between gut microbiota composition and hypertension, highlighting the potential for dietary interventions, probiotics, prebiotics, physical activity and FMT as therapeutic strategies. Summary: This review underscores the promise of microbiota-targeted therapies in managing hypertension and calls for further research to elucidate precise mechanisms and develop personalized medicine approaches. Understanding the complex interactions between gut microbiota and hypertension could pave the way for innovative treatments and improved cardiovascular health outcomes.